An automatic marine-organism monitoring system for the intake water of the nuclear power plant. (November 2017) - Tang, Zhihong; Cheng, Feng; Jin, Xiaoxiang; Sun, Li; Bao, RuoYu; Liu, Yang
Highlights: An automatic system for the marine-organism monitoring at NPP is proposed. A 2D sonar and an underwater camera are integrated for organism detection. The automatic control system and remote control strategy is designed. The system is realized to monitor the invade and avoid NPP accident efficiently. Abstract: On a review of the nuclear power plant accidents caused by marine organism intrusion and current strategies used by the NPPs, a complete set of marine-organism monitoring system for the water-intake of the nuclear power station was designed. The system integrates sonar and high-definition camera as the detecting equipment to have wide detection range of the marine organism. Integrated with automatic inspecting instruments and data transmission networks, the system can realize the automatic inspection with different depth, different directions and different time periods.